2014
DOI: 10.1002/ptr.5247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ginkgo Biloba Extract on Lipopolysaccharide-induced Anhedonic Depressive-like Behavior in Male Rats

Abstract: The peripheral administration of lipopolysaccharide (LPS) induces depressive-like behavior. Anhedonia is a core symptom of depression, defined as a loss of the capacity to experience pleasure. The present study used the sucrose preference test to investigate the influence of Ginkgo biloba extract (EGb 761) on LPS-induced anhedonia in male rats. The animals were randomly divided into four groups: (I) vehicle + saline, (II) vehicle + LPS, (III) EGb 761 + saline, and (IV) EGb 761 + LPS. Saline or LPS (100 μg/kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 67 publications
0
24
0
2
Order By: Relevance
“…For example, single injections of septic doses of LPS (5 mg/ kg) cause progressive neurodegeneration of the nigrostriatal DArgic system (Qin et al, 2007;Reinert et al, 2014). It should be noted that acute systemic administration of low-dose LPS (~100 μg/kg) has been reported to either decrease tissue DA content or increase extracellular DA metabolites in the NAcc (van Heesch et al, 2014;Yeh et al, 2015). However, these studies assessed DA and 'anhedonic' behavior (sucrose preference or responding for brain stimulation) at 2-4 h post LPS (van Heesch et al, 2014;van Heesch et al, 2013;Yeh et al, 2015), a time point that may be confounded due to the febrile effects of LPS and related sickness behaviors (Dinarello, 2004;Frenois et al, 2007;O'Connor et al, 2009b).…”
Section: Biochemical and Behavioral Studies In Laboratory Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, single injections of septic doses of LPS (5 mg/ kg) cause progressive neurodegeneration of the nigrostriatal DArgic system (Qin et al, 2007;Reinert et al, 2014). It should be noted that acute systemic administration of low-dose LPS (~100 μg/kg) has been reported to either decrease tissue DA content or increase extracellular DA metabolites in the NAcc (van Heesch et al, 2014;Yeh et al, 2015). However, these studies assessed DA and 'anhedonic' behavior (sucrose preference or responding for brain stimulation) at 2-4 h post LPS (van Heesch et al, 2014;van Heesch et al, 2013;Yeh et al, 2015), a time point that may be confounded due to the febrile effects of LPS and related sickness behaviors (Dinarello, 2004;Frenois et al, 2007;O'Connor et al, 2009b).…”
Section: Biochemical and Behavioral Studies In Laboratory Animalsmentioning
confidence: 99%
“…It should be noted that acute systemic administration of low-dose LPS (~100 μg/kg) has been reported to either decrease tissue DA content or increase extracellular DA metabolites in the NAcc (van Heesch et al, 2014;Yeh et al, 2015). However, these studies assessed DA and 'anhedonic' behavior (sucrose preference or responding for brain stimulation) at 2-4 h post LPS (van Heesch et al, 2014;van Heesch et al, 2013;Yeh et al, 2015), a time point that may be confounded due to the febrile effects of LPS and related sickness behaviors (Dinarello, 2004;Frenois et al, 2007;O'Connor et al, 2009b). These early effects of LPS may also reflect, for instance, acute activation of neuroendocrine peptides and hormones (minutes to hours), which can have stimulatory effects on turnover or release of brain catecholamines (Barrot et al, 2000;Lavicky and Dunn, 1993;Matsuzaki et al, 1989;Mekaouche et al, 1996), and which may occur ahead of the more chronic mechanisms by which inflammation is thought to contribute to decreased DA availability (see the section 'Mechanisms of inflammation effects on dopamine synthesis and release' below for detailed discussion).…”
Section: Biochemical and Behavioral Studies In Laboratory Animalsmentioning
confidence: 99%
“…Our previous study and Yeh et al . study found that EGb761 attenuated the depressive-like behaviours induced by lipopolysaccharide injection [1, 31]. However, it has not been studied whether EGb761 has antidepressant-like activities in the light deprivation-induced animal model of depression, which has unique immunological features.…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo investigation was conducted to assess anhedonia as a main symptom of depressive disorders by sucrose preference test after injection of saline, LPS (100 μg/kg), EGb761 (50 mg/kg for 2 weeks), LPS, and EGb761 concomitantly in rats. This study showed that GBLE could significantly inhibit anhedonia induction in the animals and compensate the dopamine decrement, which was due to the LPS administration, but it was not able to increase the low level of serotonin significantly (Yeh et al, ).…”
Section: Natural Toxinsmentioning
confidence: 98%